Post Method Pedagogy: Opportunities and Challenges in EFL Context of Nepal - Sapkota, Narayan Prasad (English Language Teaching Perspectives, 2022)
Post-method pedagogy is an attempt to go beyond the quest of the best method or method-based restrictions in language teaching. Pedagogy in these premises is not limited to classroom activities, teaching materials, curricular objectives, and evaluation procedures, but also covers traditionally overlooked areas such as historical, political and socio-cultural experience. It is a tripartite system with the three pedagogic parameters such as particularity, practicality, and possibility. This research was conducted to explore the opportunities and challenges of adopting post method pedagogy in the EFL context of Nepal. The research uses document analysis and auto ethnographic evidences as the source of data. The analysis of data results that the application of three pedagogic parameters of post method pedagogy is an opportunity to improve the EFL practices in Nepal. The research also indicates that there are diverse challenges to bring these pedagogies into practice. This research implies the urgency of post method pedagogy for improving EFL situation of Nepal is urgent.